Improvement Communicational Skills (Reading, Writing, Speaking) In ESP Classes of Andijan State Medical Institute (Eurasian Scientific Herald, 2022)
There is a rapid and intensive development of medical science. In accordance with this, new goals and objectives are being put forward in the training of medical specialists, which are reflected in Uzbek standards of higher professional medical education (ASMI). These goals and objectives concern not only specialized medical disciplines, but also disciplines of the basic general education cycle. The article discusses the concept of listening; the relationship with other types of speech activity, the types and stages of listening, and also provides example exercises for the development and improvement of this skill in Andijan state medical institute (ASMI) among pharmacy students.